Pentingnya Perencanaan Bisnis Bagi Pengusaha Klanting di Desa Banuayu Kec. BP. Peliung Kab. OKU Timur - Siti Afifah; Khafid Ismail; Irawan . (Jurnal Indonesia Mengabdi, 2020)
The purpose of this study is to describe the importance of planning for Klanting entrepreneurs in the village of Banuayu Kec. BP Peliung Kab. East OKU. The data source in this research is the people of Banuayu village who make klanting. This research is included in field research (Field Research) using a qualitative approach that is described descriptively, this research contains an overview of the understanding of the importance of business planning for entrepreneurs. This study also describes the importance of business planning for entrepreneurs. Data collection methods used were observation and interview methods. The results of this study indicate that in making the effort, planning is very much needed. Not only do we just start a business that is important to run, we don't think about the future.